Snow and temperature regime of a perennial ice patch, Ward Hunt Island, Nunavut, Canada. ... : Le régime d’enneigement et de température d’une plaque glace permanente, île Ward Hunt, Nunavut, Canada. ... - Fortier, Daniel; Davesne, Gautier (Nordicana D, 2021)
Long-term monitoring of an ice patch at Ward Hunt Island on the northern coast of Ellesmere Island (83°06'N 074°10'W; Nunavut, Canada) provides information on the seasonal and interannual evolution of these cryospheric elements The ice internal temperature was measured since July 2017 by a chain of thermistors (YSI; accuracy ± 0.1 °C; resolution ± 0.001°C) at depths of 50, 100, 150, 200, 250, 300 and 320 cm installed in a borehole 7 cm in diameter in the ice patch IP1 (83°05'38.39''N; 74°11'58.62''). A white perforated plastic pipe (PVC; 3 cm in diameter) was inserted into the borehole in which the cable was inserted. Slush (mix of water and snow) was then poured in and around the pipe to set it and guarantee an optimal thermal contact with the ice body. The deepest thermistor, at 320 cm, was in contact with the ground surface (weathered bedrock). The thermistors were connected to a multichannel data logger (Systems Smart Reader Plus 8™, ACR Systems Inc.). The ice surface temperature (0 cm) was recorded by a ... : La surveillance à long terme d'une plaque de glace à l'île Ward Hunt sur la côte nord de l'île d'Ellesmere (83°06'N 074°10'W; Nunavut, Canada) fournit des informations sur l'évolution saisonnière et interannuelle de ces éléments cryosphériques. La température de la glace a été mesurée depuis juillet 2017 par une chaîne de thermistances (YSI; précision ± 0,1 °C; résolution ± 0.001°C) à des profondeurs de 50, 100, 150, 200, 250, 300 et 320 cm installées dans un trou de forage de 7 cm de diamètre dans la plaque de glace IP1 (83°05'38.39''N 74°11'58.62''). Un tuyau en plastique perforé blanc (PVC; 3 cm de diamètre) a été inséré dans le trou de forage dans lequel le câble a été inséré. Un mélange d'eau et de neige a ensuite été versé dans et autour du tuyau pour le fixer et garantir un contact optimal avec le corps de glace. La thermistance la plus profonde, à 320 cm, était au contact avec la surface du sol (roche-mère altérée). Les thermistances ont été connectées à un enregistreur de données multicanaux ...